2018
DOI: 10.12809/hkmj177111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of paternal age on semen parameters and live birth rate of in-vitro fertilisation treatment: a retrospective analysis

Abstract: To determine the effect of paternal age on semen parameters and the live birth rate from invitro fertilisation (IVF) treatment. Methods: We performed a retrospective cohort study of couples undergoing a first IVF cycle between 2004 and 2014 in a tertiary assisted reproduction centre in Hong Kong. Results: We analysed 3549 cases. Paternal age ≥40 years was negatively correlated with semen volume, progressive motility, total motility and total normal motile count (P<0.005) and positively correlated with sperm co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
2
5
0
2
Order By: Relevance
“…The prognostic reliability of male semen analysis for success with ART is poor 38 . We observed that all parameters, except morphology, of semen analysis deteriorated with increasing male age, as has been shown previously 14,39 . Semen analysis quality was consistent across most male ages in our study up to age 50 years, with approximately 60% of men achieving values within the reference range according to the WHO criteria 24 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The prognostic reliability of male semen analysis for success with ART is poor 38 . We observed that all parameters, except morphology, of semen analysis deteriorated with increasing male age, as has been shown previously 14,39 . Semen analysis quality was consistent across most male ages in our study up to age 50 years, with approximately 60% of men achieving values within the reference range according to the WHO criteria 24 .…”
Section: Discussionsupporting
confidence: 78%
“…38 We observed that all parameters, except morphology, of semen analysis deteriorated with increasing male age, as has been shown previously. 14,39 Semen analysis quality was consistent across most male ages in our study up to age 50 years, with approximately 60% of men achieving values within the reference range according to the WHO criteria. 24 Over 50 years of age, only 42% of men met the WHO criteria for semen analysis across all parameters.…”
Section: Discussionsupporting
confidence: 66%
“…Выявленное у обследованных нами мужчин возраст-ассоциированное снижение объема эякулята согласуется с данными литературы [7,28] и может быть связано с возрастным изменением работы предстательной железы. Количество сперматозоидов в эякуляте также статистически значимо снижается с возрастом.…”
Section: Discussionunclassified
“…Возможно также негативное влияние на сперматогенез заболеваний различных органов и систем [29], количество и тяжесть которых существенно повышаются с возрастом человека. Имеющиеся в литературе сведения противоречивы: в исследовании [28] показано, что с возрастом происходит увеличение концентрации сперматозоидов и не изменяется их общее количество в эякуляте; согласно другим работам [10,30] -концентрация и количество сперматозоидов стабильны и эти показатели не связаны с возрастом. По данным российских авторов [13], у бесплодных мужчин старше 45 лет также выявлено снижение количества сперматозоидов в эякуляте.…”
Section: Discussionunclassified
“…Since that review, a number of larger cohort studies have been performed, however, the results of these studies have been contradictory. Some studies have found that paternal age has a detrimental effect on outcome (19)(20)(21)43) and others have not found evidence of a detrimental effect (21,30,44,45). A systematic review of studies performed using the donor egg model suggested that advancing paternal age is not associated with adverse oocyte donation outcomes (17).…”
Section: Discussionmentioning
confidence: 99%